Prevalence of Gingival Pigmentation and its Association with Gingival Biotype and Skin Colour - Rijal, Arjun Hari; Dhami, Bhageshwar; Pandey, Nashib; Aryal, Deepa (Journal of Nepalese Society of Periodontology and Oral Implantology, 2021)
Introduction: The facial appearance depends on several oral and extraoral factors including colour of facial skin and pigmentation of gingival epithelium. The colour of the gingiva varies among individuals and is thought to be associated with cutaneous pigmentation which ranges from light to dark brown or black colour. Objective: To assess the prevalence of physiological gingival pigmentation, gingival biotype and their association with skin colur in Nepalese subjects visiting Kantipur Dental College and Hospital (KDCH). Methods: This was an analytical cross-sectional study which was carried out from February 2020 to June 2020 in all patients of age-group 16 to 80 years visiting the Department of Periodontics at KDCH after ethical approval. Patients were recruited by convenience sampling and examined thoroughly to find out gingival biotype and extent of gingival pigmentation intraorally as well as skin colour extraorally. Results: In this study, 210 patients were examined among which, 105 (50%) were males and 105 (50%) were females. Out of 210, 33 (15.7%) had pink tissue without pigmentation, 84 (40%) had pigmentation only in attached gingiva, 58 (27.6%) in attached gingiva and interdental papilla, 32 (15.2%) had diffuse pigmentation involving all parts of gingiva, 2 (1%) had in marginal gingiva only, and 1 (0.5%) in marginal gingiva and interdental papilla. Conclusion: A strong association was found between gingival pigmentation and facial skin colour in present study (P <0.001). Establishing the pattern of gingival pigmentation in Nepalese population will help to choose a specific depigmentation therapy that will harmonise with skin colour.